2023
DOI: 10.3390/buildings13082059
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Construction: A Systematic Review of Circular Economy Strategies and Ecodesign in the Built Environment

Abstract: This review discusses the unsustainable nature of current production and consumption patterns, particularly in the civil construction sector. To address this, the circular economy model has been proposed as a solution, but the impact reduction of circular strategies (CS) is not well understood. Thus, aligning CS with ecodesign can help achieve sustainable development. We conducted a systematic review of studies on CS and ecodesign strategies (ES) in the built environment, which led us to identify 23 essential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 101 publications
0
5
0
Order By: Relevance
“…Reusing secondary materials and components in new productions appears as the most cited CE practice during the manufacturing stage. Agreeing with that, Eberhardt, Birkved [23] and Timm, Maciel [60] identified that the most common CE strategies in the construction sector are related to reusing materials. It also reduces the energy consumption of the manufacturing processes in the construction industry and other industries [26].…”
Section: Surveys + Expert Forumsmentioning
confidence: 88%
See 1 more Smart Citation
“…Reusing secondary materials and components in new productions appears as the most cited CE practice during the manufacturing stage. Agreeing with that, Eberhardt, Birkved [23] and Timm, Maciel [60] identified that the most common CE strategies in the construction sector are related to reusing materials. It also reduces the energy consumption of the manufacturing processes in the construction industry and other industries [26].…”
Section: Surveys + Expert Forumsmentioning
confidence: 88%
“…Thus, this study categorised the same under the 'other' category of CE practices. A passport for a material is a collection of data and indicators that enhances the transparency of material or system properties and assists in measuring and optimising its effectiveness [7,60,63]. Applying take-back and trade-in systems is another well-cited CE practice in the literature, which relates to the CE business model context.…”
Section: Surveys + Expert Forumsmentioning
confidence: 99%
“…Implementing CE strategies in the construction sector promises numerous benefits, including but not limited to cost reduction, environmental preservation, and the enhancement of societal well-being [10,16,19,20]. Furthermore, CE can play a vital role in contributing to the sustainability in the sector [20]. According to Pomponi and Moncaster [21], circular construction involves elements/systems that extend their lifespans and reduce waste.…”
Section: Circular Economy In the Construction Industrymentioning
confidence: 99%
“…Waris, M., et al, 2014 [59] largely researched on onsite mechanization in Malaysian construction. Timm, J.F.G et al, 2023 [60] adopted a framework in the sequence of Plan-Do-Check-Act to support trade-offs in collaborative decision-making. While Gamage, I. et al, 2024 [61] identified the relationships of highly cited circular practices in the literature, Karaca, F et al, 2024 [62] explained the concept of resource equity in the construction sector.…”
Section: Theoretical Contributionmentioning
confidence: 99%